End-binding protein 1 regulates the metabolic fate of CD4+ T lymphoblasts and Jurkat T cells and the organization of the mitochondrial network - Gómez-Morón, Álvaro; Requena, Silvia; Pertusa, Clara; Lozano-Prieto, Marta; Calzada-Fraile, Diego; Scagnetti, Camila; Sánchez-García, Inés; Calero-García, Ana Adela; Izquierdo, Manuel; Martín-Cófreces, Noa B. (Frontiers in Immunology, 2023)
The organization of the mitochondrial network is relevant for the metabolic fate of T cells and their ability to respond to TCR stimulation. This arrangement depends on cytoskeleton dynamics in response to TCR and CD28 activation, which allows the polarization of the mitochondria through their change in shape, and their movement along the microtubules towards the immune synapse. This work focus on the role of End-binding protein 1 (EB1), a protein that regulates tubulin polymerization and has been previously identified as a regulator of intracellular transport of CD3-enriched vesicles. EB1-interferred cells showed defective intracellular organization and metabolic strength in activated T cells, pointing to a relevant connection of the cytoskeleton and metabolism in response to TCR stimulation, which leads to increased AICD. By unifying the organization of the tubulin cytoskeleton and mitochondria during CD4+ T cell activation, this work highlights the importance of this connection for critical cell asymmetry together with metabolic functions such as glycolysis, mitochondria respiration, and cell viability.